Prescribed underburning before resin tapping does not affect resin yield in Pinus pinaster Ait. stands - Javier Madrigal; Cristina Carrillo-García; Aida Rodríguez-García; David González-Sancho; Mercedes Guijarro; Juncal Espinosa; Carmen Hernando; Celia García-Feced (Forest Systems)
Aim of study: To assess the effect of prescribed underburning (PB) and tapping on resin yields in maritime pine stands. We hypothesized that PB reduces fire hazard, generates stress at the cambium level and potentially increases the number of resin canals and resin yield after tapping.